Mid-Upper arm circumference in pregnant women and its correlation to birth weight - Indriyani, Indriyani; Oktariza, Rury Tiara; Noviyanti, Noviyanti; Virginia, Jessica Aurel (Muhammadiyah Medical Journal, 2023)
Background: During pregnancy, there is an increase in maternal metabolism, which affects the growth of the fetus and fetal organs. Pregnant women who cannot meet nutritional needs can risk experiencing problems with poor nutritional status. This adversely affects the baby and the mother. One of the anthropometric measurements commonly used to assess pregnant women's nutritional status is measuring the Mid Upper Arm Circumference (MUAC). Pregnant women with MUAC interpretation less than 23.5 cm are said to be at risk of chronic energy deficiency (CED). Purposes: This study aimed to determine the relationship between the MUAC of pregnant women and the baby's body weight. Methods: The research methodology used analytical observational with a cross-sectional approach to the medical records of 104 mothers at the Taman Baca Health Center, Pembina Health Center, and Plaju Palembang Health Center. Data were collected by purposive sampling. Result: The results of this study showed that MUAC for pregnant women was more than equal to 23.5 cm as many as 86 (82,7%) respondents, while pregnant women of MUAC were less than 23.5 cm as many as 18 (17,3%) respondents. Analysis with Fisher's Exact Test with p-value=1,000. Conclusion: there was no meaningful relationship between the MUAC of pregnant women and the body weight of babies.